(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Diabetes associated with pancreatitis is an increasingly recognized health concern, primarily arising secondary to pancreatic diseases, with chronic pancreatitis being the most prevalent cause. In Ayurvedic terms, diabetes mellitus (Prameha) is associated with Kapha and Pitta vitiation, whereas pancreatitis is linked to aggravated Pitta disrupting Agni (digestive fire) and leading to Amaaccumulation. Ayurvedic management integrates di etary modifications, Ayurvedic formulations, and Panchakarma therapies to restore metabolic balance and enhance pancreatic function. This study presents the case of a 29-year-old male diagnosed with Diabetes Mellitus associated with pancreatitis, who sought treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi, Punjab. He underwent Panchakarma thera pies, including Awagah Swedan, Madhu Tailik Basti, Shiropichu with Brah mi oil, and Nasyam with Anutaila, alongside Ayurvedic formulations. Fol lowing Ayurvedic treatment, the patient experienced significant symptom relief, improved glycemic control, and better laboratory parameters, includ ing reduced HbA1C levels and improved liver enzyme markers. These find ings highlight the potential of Ayurvedic interventions in managing diabetes associated with pancreatitis. However, further clinical trials are necessary to validate these outcomes and establish standardized treatment protocols for enhanced patient care.